Pompeii's secret underworld [videorecording (DVD)] - Boffey, Mercer, 1982- (PBS, 2025)
"For over two centuries, archaeologists have hailed Pompeii as a sophisticated city at the heart of an advanced ancient civilization. But a series of new excavations is painting a much more complex picture of the city tragically buried by the eruption of Mount Vesuvius in the year 79. New archaeological finds - including 2,000-year-old lines of graffiti, human remains, and artifacts from ancient homes and businesses - are revealing a city of both staggering wealth as well as abject poverty, dependent on slavery, and torn apart by political rivalries, violence, and riots. Even before Vesuvius rumbled, the jewel of the ancient Roman Empire hid a very dark side"--Container.